Actualization of Islamic Religious Education in Relationship with Emotional Spiritual Quotient of Muslim Adolescents in Bandung City - Mauditya, Anggie; Komalasari, Nisa; From, Princess Wulan; Khairunnisa, Sheila Susanti; Qory, Ananda Leila; Hernawati, Hernawati (Universitas Islam Sultan Agung, 2024)
Islamic religious education has an important role in shaping the personality and morality of individuals, especially teenagers, in facing the complexities of modern life. This research aims to explore the relationship between the actualization of Islamic Religious Education and the Emotional Spiritual Quotient (ESQ) in Muslim adolescents in the city of Bandung. This research uses a survey design with a direct interview method and distributing instruments by filling out questionnaires. Apart from that, this research also collected data using documentation study techniques from various news stories on Muslim Youth in Bandung City. The approach method in the Islamic Religious Education actualization program can strengthen the relationship with the Emotional Spiritual Quotient (ESQ) in Muslim teenagers in the city of Bandung. The results of the research show that there is a strong relationship between Islamic Religious Education and ESQ among Muslim teenagers in the city of Bandung. This research also found that a holistic approach, such as the use of inspiring Islamic stories, the formation of a supportive community, and direct experience in the practice of worship, can help Muslim teenagers develop their emotional and spiritual well-being as a whole. It is hoped that the results of this research can increase emotional and spiritual intelligence in Muslim adolescents through Islamic Religious Education and can be used as evaluation material for follow-up in the teaching of Islamic Religious Education